2013
DOI: 10.1177/0973408213495609
|View full text |Cite
|
Sign up to set email alerts
|

Embracing the Paradox in Educational Change for Sustainable Development: A Case of Accounting

Abstract: Higher education institutions have been encouraged to prepare their graduates to be socially and environmentally responsible professionals. However, previous studies have found a slow uptake of education for sustainable development (ESD) in university curricula, particularly in nonenvironmental disciplines. This paper investigates the process of developing educational change for sustainability in an Australian university and the impact of such development on an area that has long been resistant to the sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Experiences from numerous projects and programmes at institutions of higher education have shown that attempts to integrate the topic of sustainability into teaching, research and operations often encounter resistance (Barber et al, 2014;Quian, 2013;Peet et al, 2004;Holmberg et al, 2008;Pesonen, 2003). This means that much valuable energy is lost and the results of projects and programmes rarely meet the expectations placed on them.…”
Section: Resultsmentioning
confidence: 99%
“…Experiences from numerous projects and programmes at institutions of higher education have shown that attempts to integrate the topic of sustainability into teaching, research and operations often encounter resistance (Barber et al, 2014;Quian, 2013;Peet et al, 2004;Holmberg et al, 2008;Pesonen, 2003). This means that much valuable energy is lost and the results of projects and programmes rarely meet the expectations placed on them.…”
Section: Resultsmentioning
confidence: 99%
“…Because environmental sustainability is inherently interdisciplinary, some have argued that it needs to be incorporated into more academic disciplines to fully educate students for environmental literacy (Svanström et al, 2008;Jucker, 2002). However, this requires faculty IJSHE 20,7 commitment from a range of disciplines to integrate sustainability into their coursework (Qian, 2013;Boyes et al, 2009;Bacon et al, 2011). Owing to the difficulties of raising awareness about sustainability in an educational context, universities have placed greater emphasis on raising awareness through operations because they are more visible, face less resistance and have potential economic benefits (Rad et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although, Higher Education (HE) must conduct research and learning for sustainable development (Koehn and Uitto, 2014), Scott et al, (2012) have posited, there is a lack of commitment to ESD in Higher Education, where ESD implementation is poor (Wei Quan, 2013). Importantly, securing top level management support is seen as critical to addressing poor ESD implementation (Wei Quan, 2013).…”
Section: Education As An Education For Sustainable Development Barriermentioning
confidence: 99%